Stem Cell Engineering 2010
DOI: 10.1007/978-3-642-11865-4_5
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cardiac Differentiation of Mouse Embryonic Stem Cells by Electrical Stimulation

Abstract: Cardiovascular diseases account for more deaths than any other illness. Cardiac tissue engineering has turned to embryonic stem cells as a renewable source of myocytes for use in tissue replacement. Existing methods for stem cell differentiation toward the cardiac lineage are relatively non-specific, yielding low numbers of myocytes with varying contraction frequencies and strengths. Here we describe novel experimental approaches, utilizing an electrical stimulation regimen, aimed at increasing the efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…The serum-free media composed of knockout Dulbecco's modified Eagle medium (KO-DMEM)/F12 medium supplemented with 0.5 • N 2 , 0.5 • B27, and 0.05% bovine serum albumin (BSA; all from Invitrogen), 50 IU/mL penicillin and 50 mg/ mL streptomycin (Cellgro), 2 mM l-glutamine (Invitrogen), 10 ng/mL human recombinant bone morphogenetic protein (BMP-4; R&D Systems), 1,000 U/mL ESGRO Ò mouse leukemia inhibitory factor (mLIF) (Millipore), and 0.15 mM 1-Thioglycerol (Sigma). Some preliminary experiments were carried out with mouse ES-D3 cells, which were cultured feeder-free, as previously described [37]. Details are provided in Supplementary Materials and Methods (Supplementary Data are available online at www.liebertpub.com/scd).…”
Section: Mesc Maintenance Culturementioning
confidence: 99%
“…The serum-free media composed of knockout Dulbecco's modified Eagle medium (KO-DMEM)/F12 medium supplemented with 0.5 • N 2 , 0.5 • B27, and 0.05% bovine serum albumin (BSA; all from Invitrogen), 50 IU/mL penicillin and 50 mg/ mL streptomycin (Cellgro), 2 mM l-glutamine (Invitrogen), 10 ng/mL human recombinant bone morphogenetic protein (BMP-4; R&D Systems), 1,000 U/mL ESGRO Ò mouse leukemia inhibitory factor (mLIF) (Millipore), and 0.15 mM 1-Thioglycerol (Sigma). Some preliminary experiments were carried out with mouse ES-D3 cells, which were cultured feeder-free, as previously described [37]. Details are provided in Supplementary Materials and Methods (Supplementary Data are available online at www.liebertpub.com/scd).…”
Section: Mesc Maintenance Culturementioning
confidence: 99%
“…However, a multitude of in vivo environmental and cellular cues that govern their functions are absent from in vitro settings. An increasing body of evidence has suggested that exogenous electrical stimuli have beneficial effects on in vitro cultured cardiomyocytes [25,26]. In this study, ITO has been used for electrical stimulation setting.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular diseases are the primary cause for death compared to other illnesses [183]. Recently, attention has been paid to generating cardiac patches [58] and heart valves as “spare parts”, and developing functional myocardial stents for cardiac repair [184]. Electrical conductivity of the PPy scaffolds has the possibility to be a critical part of cardiac and neural tissue engineering.…”
Section: Electroactive Polymers For Tissue Regeneration Applicationsmentioning
confidence: 99%
“…Electrical conductivity of the PPy scaffolds has the possibility to be a critical part of cardiac and neural tissue engineering. Electrical stimulation producing a reaction is a pivotal characteristic of neuron and myocyte differentiation and function [27,28,58] (Figure 8). Recently, cardiac differentiation has been promoted by using porous and fibrous scaffolds or 2D substrates incorporated with PPy or PANi [5962,185].…”
Section: Electroactive Polymers For Tissue Regeneration Applicationsmentioning
confidence: 99%
See 1 more Smart Citation